Believe me! Why tesla’s recent alleged malfunction further highlights the need for transparent dialogue - Milford, Stephen R.; Elger, Bernice S.; Shaw, David M. (Frontiers in Future Transportation, 2023)
On November the 13th, 2022 video footage was released purportedly showing a Tesla Model Y malfunctioning by speeding through the streets of a Chinese city killing two people. Video footage such as this has the potential to undermine trust in AVs. While Tesla has responded by stating they will get to the ‘truth,’ there are questions as to how this truth is to be decided, and perhaps more importantly how the public can trust either Tesla or negative press. We explore the ‘facts’ of the incident and discuss the challenges of building trust in new AVs systems based on transparency. In this article we argue that transparency is more than simply getting to the ‘truth.’ It is fostering a relational dialogue between the facts and stakeholder. Using O’Brien’s window metaphor, this article explores the need for AV manufacturers to consider the content of such incidents, the different perceptions of stakeholders, and the medium through which the content is presented. Apart from the need for independent crash investigators, there is a need for AV manufacturers to go beyond simply’ getting to the truth’ and to engage with the public responsibly.